Effect comparison of neuroendoscopic vs. craniotomy in the treatment of adult intracranial arachnoid cyst - Liang, Jianfeng; Li, Kai; Luo, Bin; Zhang, Jun; Zhao, Peng; Lu, Changyu (Frontiers in Surgery, 2023)
Purpose: Intracranial arachnoid cysts are common intracranial space-occupying lesions, accounting for about 1-2% of Intracranial space-occupying lesions. There is controversy over the method of surgical intervention. In order to provide guidance for surgical decision-making, this study compares the efficacy of craniotomy versus neuroendoscopic surgery in treating arachnoid cysts. Methods: The adult patients with arachnoid cyst admitted to our department from October 2016 to August 2021 were retrospectively analyzed. Thirteen adult patients were recruited, and divided into neuroendoscopic group (group A) and craniotomy group (group B). We compared the gender, age, clinical symptoms, preoperative and postoperative cyst size, symptom improvement, complications, length of hospital stay and hospital costs between two groups to analyze the therapeutic effects of these two surgical methods. Results: The cost of hospitalization in group A was significantly lower than in group B (47292.8 vs 65151.8 yuan, P ＜ 0.05), and there was no difference in the length of hospital stay between the two groups. The preoperative cysts in group A were significantly larger than those in group B (6.38 vs 2.97cm, P ＜ 0.05). In group A and group B the short-term symptom improvement rates were 100% and 75.0% respectively. The long-term symptom improvement rates were 77.78% and 75.0% (P>0.05) respectively. Conclusion: Both neuroendoscopic and craniotomy have good curative effects for the treatment of intracranial arachnoid cysts. There was no significant difference in the outcomes between the two surgical techniques. The cost of hospitalization can be reduced with neuroendoscopic surgery. Neuroendoscopic treatment is recommended for large intracranial arachnoid cysts, and craniotomy is suitable for small intracranial arachnoid cysts.